Eneolithic pile dwellings south of the Alps precisely dated with tree-ring chronologies from the north - Čufar, Katarina; Tegel, Willy; Merela, Maks; Kromer, Bernd; Velušček, Anton (Dendrochronologia, 2015)
We present dendrochronological dating of Eneolithic pile dwellings on Ljubljansko barje, Slovenia, from the 4th millennium BC, partly included on the UNESCO world heritage list in 2011. Samples of oak (Quercus sp.) timbers from the posts on which the dwellings were built have been collected over the past 20 years. They have been dendrochronologically cross-dated and (pre) dated by 14C wiggle-matching. We describe the construction of a 442-year chronology BAR-3330 based on 106 cross-dated tree-ring series of wood from six pile-dwelling sites. Comparison of BAR-3330 with reference chronologies of more than 500km distant areas north of the Alps showed that it can be teleconnected and dated with a combined German Swiss chronology. The time span of BAR-3330 was defined in this way as 3771-3330 BC. We were thus able to date exactly building activities on the pile dwellings Strojanova voda (SV), Hočevarica (HO), Maharski prekop (MP), Črešnja pri Bistri (CR), Spodnje mostišče (SM) and Stare gmajne (SG), in which early copper metallurgy played an important role. This is the first dendrochronological dating of prehistoric pile dwellings south of the Alps using reference chronologies from the north based on teleconnection. It provides an opportunity to continue filling the spatial and temporal gaps in the absolute chronology of the 4th millennium BC in the area south and south east of the Alps.
Gesehen am 15.12.2020